2020
DOI: 10.1101/2020.06.23.165191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal whole-brain dynamics of auditory patterns recognition

Abstract: Music is a universal non-verbal human language, built on logical structures and articulated in balanced hierarchies between sounds, offering excellent opportunities to explore how the brain creates meaning for complex spatiotemporal auditory patterns. Using the high temporal resolution of magnetoencephalography in 70 participants, we investigated their unfolding brain dynamics during the recognition of Johann Sebastian Bach's original musical patterns compared to new variations thereof. Remarkably, the recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 80 publications
2
26
0
Order By: Relevance
“…Furthermore, music listening, besides involving the drive to move (with dancing), is in and of itself a memory process: when we listen, we implicitly encode repeated melodic and rhythmic patterns, and are able to recognise them later on. In a recent study, we identified the systemic brain network changes in temporo-frontal brain areas, including the hippocampus, associated with these memory processes [ 163 ] ( Figure 2 ). Future research could proceed in this direction and determine whether BDNF-related neuroplastic processes and the associated brain network changes could be triggered simply by passive exposure, namely by just listening to music without playing, as animal studies seem to indicate.…”
Section: Boosting Endogenous Bdnf: Musicmentioning
confidence: 99%
“…Furthermore, music listening, besides involving the drive to move (with dancing), is in and of itself a memory process: when we listen, we implicitly encode repeated melodic and rhythmic patterns, and are able to recognise them later on. In a recent study, we identified the systemic brain network changes in temporo-frontal brain areas, including the hippocampus, associated with these memory processes [ 163 ] ( Figure 2 ). Future research could proceed in this direction and determine whether BDNF-related neuroplastic processes and the associated brain network changes could be triggered simply by passive exposure, namely by just listening to music without playing, as animal studies seem to indicate.…”
Section: Boosting Endogenous Bdnf: Musicmentioning
confidence: 99%
“…Although previous work on naturalistic music has correlated neural and physiological responses to dynamically changing acoustic features [1][2][3]50 , or extracted epochs based on information content in the music 12 , perhaps a more robust way to identify systematic responses to naturalistic stimuli is through analysing synchrony of responses 10,[55][56][57] , in particular via inter-subject correlation (ISC, see review 58 ). This method -in which (neural) responses are correlated across participants exposed to naturalistic stimuli 59 -is based on the assumption that signals not related to processing stimuli would not be correlated.…”
Section: Introductionmentioning
confidence: 99%
“…The spheres model represented the MNI-co-registered anatomy as a simpler geometric model, allowing each sensor to be fitted with its own sphere (Hillebrand & Barnes, 2005). Finally, the beamforming used a diverse set of weights sequentially applied to the source locations to isolate the contribution of each source (brain voxel) to the activity recorded by the MEG channels for each time-point in order to isolate the contribution of each source (brain voxel) to the activity recorded by the MEG channels for each time-point (Bonetti et al, 2020; Brookes et al, 2007; Hillebrand & Barnes, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Then, we considered significant the original clusters that had a size bigger than the 99.9% of cluster sizes forming the reference distribution. Additional details on the MCS algorithm can be found in (Bonetti, Brattico, Bruzzone, et al, 2021;Bonetti, Brattico, Carlomagno, et al, 2021;Bonetti et al, 2020;Bruzzone et al, 2021).…”
Section: Brain Activity Underlying Listening To Infant Versus Adult Crymentioning
confidence: 99%